The Standards of Judgment for Dispute Resolution in Financial ADR of Japan - Yanase, Shuji (Columbia Journal of Asian Law, 2013)
Japan’s modern financial alternative dispute resolution (ADR) system was established by a series of revisions to 17 separate financial and banking statutes. While the revisions established a system in which financial disputes could be heard, they were notably silent on the standards for judgment. This article seeks to extrapolate those standards. First, this article looks towards the standards of judgment used for general ADR. I begin by establishing the historical context of ADR in Japan, followed by analyzing Japan’s modern ADR laws. I describe, in detail, key provisions from the ADR Promotion Act, the Civil Conciliation Act, and the Arbitration Act, with a particular focus on the requirements for “rule of law.” Second, I analyze the financial ADR laws of the United Kingdom and how the courts have interpreted standards of judgment for those laws. Third, I attempt to extrapolate standards of judgment for financial ADR in Japan by looking towards the “purpose” provisions of the various financial / banking laws. I analyze the purpose of the financial ADR system in light of the needs of disputing parties and with a view towards the underlying administrative goals of the government agencies responsible for the supervision of financial service providers. I further apply, by analogy, the key provisions of the Civil Conciliation Act to further refine my interpretation. I conclude that there are no rigid standards. Rather, judgments ought to be made in accordance with the “fair and reasonable (Jori),” which is a reflection of the “common sense” prevailing in society or “good sense” prevailing in the relevant financial service industries. In addition, judgments should be made with the aim towards maintaining the public’s trust in financial services. Insofar as these standards are satisfied, judgments can depart from application of statutory laws or court precedents. In light of these extrapolations, this article concludes with a checklist of requirements for financial ADR judgments. These checklists are a combination of the positive and negative requirements extrapolated from relevant ADR laws, the purpose of the financial / banking laws, and the needs for disputing parties.